2023
DOI: 10.26828/cannabis/2023.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Population and Neighborhood Correlates of Cannabis Dispensary Locations in Oklahoma

Abstract: Background: Cannabis dispensaries have proliferated exponentially in Oklahoma since the state legalized medical cannabis in 2018. Oklahoma is unique from many other legalized states given its high number of lower income, rural, and uninsured residents, who may seek medical cannabis as an alternative to traditional medical treatment. Methods: This study examined demographic and neighborhood characteristics associated with dispensary density (n = 1,046 census tracts) in Oklahoma. Results: Compared to census trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…It may be that those communities with less access to MMJ dispensaries also have less access to specialty care and treatment that was not captured in our analyses. In Oklahoma, for example, Cohn and colleagues [ 12 ] reported that census tracts with at least one dispensary (vs. none) had a greater number of hospitals and pharmacies. Limited access to traditional health care for these conditions could motivate people living in such communities to seek MMJ as an alternative treatment option or could make clinicians more likely to certify for conditions that lack evidence supporting the use of MMJ (i.e., would be better managed in a more traditional health care setting).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It may be that those communities with less access to MMJ dispensaries also have less access to specialty care and treatment that was not captured in our analyses. In Oklahoma, for example, Cohn and colleagues [ 12 ] reported that census tracts with at least one dispensary (vs. none) had a greater number of hospitals and pharmacies. Limited access to traditional health care for these conditions could motivate people living in such communities to seek MMJ as an alternative treatment option or could make clinicians more likely to certify for conditions that lack evidence supporting the use of MMJ (i.e., would be better managed in a more traditional health care setting).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with studies in California and Colorado, we did not observe an association between median income and geographic access to MMJ dispensaries [ 13 , 14 ]. However, in Oklahoma, higher proportions of residents living poverty and uninsured were associated with geographic access to MMJ dispensaries [ 12 ]. In New York State [ 11 ], census tracts with a higher proportion of residents with bachelor’s degrees or higher were more likely to have at last one certifying provider than those with less education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, in 2022, the state legislature placed a pause on new business licenses through August 1, 2024. Currently, the number of dispensaries in Oklahoma is greater than in any other state that allows medical cannabis [ 2 ]. Oklahoma has surpassed the number of dispensaries in California [ 3 ]; a significantly larger state, with over 39.2 million people compared to Oklahoma’s population of 4.0 million [ 2 ].…”
Section: Introductionmentioning
confidence: 99%